Validity of Property Sale and Purchase Agreement between Residents in Taman Duren Sawit Housing with Developer PT Altan Karsaprisma as a Result of a Lawsuit by a Third Party - Muhammad Ihab Ramadhan; Ridha Wahyuni (Borong Newinera Publisher, 2024)
This research aims to examine the validity of land and building sales and purchase agreements between residents at the Taman Duren Sawit Housing Complex (buyers) and developers (sellers), due to a lawsuit by a third party. This research is normative juridical, which uses a statutory approach (statute approach) and a case approach. The results of this research indicate that the developer as the seller has violated the objective conditions for the validity of the agreement, especially the conditions of